Constitutive heterochromatin controls nuclear mechanics, morphology, and integrity through H3K9me3 mediated chromocenter compaction - Gianna Manning; Andy Li; Nebiyat Eskndir; Marilena Currey; Andrew D. Stephens (Nucleus)
Aberrant nuclear morphology is a hallmark of human disease and causes nuclear dysfunction. Perturbed nuclear mechanics via reduced heterochromatin weakens the nucleus resulting in nuclear blebbing and rupture. While the role of heterochromatin is known, the separate roles of constitutive heterochromatin methylation states remains elusive. Using MEF and HT1080 cells, we isolated the individual contribution of constitutive heterochromatin H3K9 methylation states through histone methyltransferase inhibitors. Inhibition of SUV39H1 via Chaetocin downregulates H3K9 trimethylation (me3), while inhibition of G9a via BIX01294 downregulates H3K9 dimethylation (me2). Overall, the loss of H3K9me3 increased nuclear blebbing and rupture in interphase nuclei due to decreased nuclear rigidity from decompaction of chromocenters. Oppositely, loss of H3K9me2 decreased nuclear blebbing and rupture with increased nuclear rigidity and more compact chromocenters. We show that facultative heterochromatin and HP1α are non-essential for chromocenter compaction. Constitutive heterochromatin provides essential nuclear mechanical support to maintain nuclear shape and integrity through chromocenter compaction.